Climate change and wheat production: A comprehensive review of challenges and adaptation strategies - Lu, Mei (Resources Data Journal, 2025)
Climate change poses multifaceted and increasingly severe threats to global wheat production, directly impacting crop growth, yield, and quality. This paper synthesizes recent findings on how major climatic factors—including rising temperatures, altered precipitation patterns, elevated atmospheric CO₂ concentrations, and sea level rise—affect wheat physiology and agronomic performance. It highlights direct and indirect stressors, such as heatwaves, drought, salinity intrusion, and extreme weather events, compromising wheat productivity and food security. Furthermore, the article discusses comprehensive and multilayered adaptation strategies, including breeding climate-resilient wheat varieties, applying gene editing technologies, intelligent water resource management, and sustainable soil and ecosystem practices. This paper provides a forward-looking perspective to guide sustainable wheat production under changing climate conditions by integrating insights from genetics, agronomy, and environmental sciences.